Immune response of γδT cells in Schistosome japonicum–infected C57BL/6 mouse liver. (December 2014) - Xie, H.; Chen, D.; Li, L.; Yu, X.; Wu, C.; Gu, H.; Tang, X.; Peng, A.; Huang, J.
Summary Systematic evaluation of the role of γδT cells during the Schistosoma japonicum infection has not been reported, despite the fact that γδT cells contribute to many infectious diseases in innate immunity. Therefore, the aim of this study was to observe the properties of γδT cells in the liver of C57BL/6 mice infected by S. japonicum. In this report, using immuno‐fluorescent histological analysis, γδT cells were found around hepatic granulomatous. Moreover, the flow cytometry results revealed that the percentage of hepatic γδT cells increased significantly after S. japonicum infection. More interestingly, a subset of CD3−γδTCR+ cells were found and markedly increased after infection. Furthermore, expression of activation markers (CD25 and CD69) and cytokine profiles were detected in these hepatic CD3+γδTCR+and CD3−γδTCR+ cells. The significantly higher level of CD69, IL‐4 and IL‐17 were observed in CD3+γδTCR+ cells after infection, suggesting that CD3+γδTCR+ cells instead of CD3−γδTCR+ cells might play a predominant role during the infection. Finally, our results indicated that the expression of NKG2D on CD3+γδTCR+ cells was higher than that on CD3−γδTCR+ cells. Collectively, γδT cells could play an important role in the liver of C57BL/6 mouse during japonicum infection.